„So Far and No Further!” – Thoughts on Legitimacy of the Hungarian Border Fence - Bartko, Robert (European Journal of Multidisciplinary Studies, 2020)
In 2015, Hungary was unexpectedly affected by the irregular migration flow, which marked a beginning of a new era in the history of the European migration – in terms of its quality and its size. The European countries have been forced to admit irregular migrants from the developing countries in increasing numbers. Mass migration – not only because of its irregular nature, but also because of its qualitative and quantitative changes – has created a major challenge for the authorities concerning the legal respones. In many countries, including in Hungary, the public opinion related to the irregular migration has forced the legislators to take the necessary measures against it in order to protect the public safety. In Hungary – although the irregular migration is a multifaceted phenomenon, therefore the legal respones affect many parts of the internal legal system – the law enforcement and the criminal law have been focused by the legislator. In the face of the increased migratory pressure - in order to protect the security of Hungary – the Hungarian government has accepted a package of the legal measures. The first step was the construction of the physical border fence at the Serbian-Hungarian and the Croatian-Hungarian border, and as a second stage the Hungarian Parliament adopted the Act CXL of 2015 which created the legal framework on protection of the mentioned border fence (for example creating new statutory definitions). Whereas not only the Hungarian Criminal Code, but also the Act of Criminal Procedure were amended by the mentioned act, it is necessary to deal whether the construction of the border fence can be considered as a legitimate step with special reference to the international and European commitments of Hungary. The mentioned question is considered as a preliminary one, because in default of legitimacy all of the measures adopted by the Hungarian Parliament and the Government would be considered unlawful. The paper deals with the mentioned problem and analyzes the legitimacy of the Hungarian border fence taking into consideration the international and European standards.